Edupreneur: Mengubah Paradigma Kewirausahaan Mahasiswa Pendidikan Matematika - Selestina Nahak; Stanislaus Amsikan (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Abstract Edupreneur activities or entrepreneurship education for students aims to: 1) Changing the paradigm, the mindset of students about entrepreneurship so that they have the skills, knowledge and attitude of entrepreneurship after completing their studies. 2). Helping students to analyze environmental-based entrepreneurial opportunities. The method used in this activity is an environmental-based business analysis activity. The service will be held on October 4, 2022. It will consist of two sessions. Session I, Motivation and introduction to the concept of entrepreneurship, and Session II of group assistance in making environmental-based business analysis. Session I aims to provide understanding and motivation for participants so they can change their mindset about entrepreneurship. And in session II it aims to train and assist participants to be actively involved in making business analysis based on real conditions, needs and opportunities in the environment. After the second session ended and based on the discussion the dedication team concluded 1). Students' understanding and knowledge about entrepreneurship can foster an entrepreneurial spirit 2). Students are able to analyze opportunities and environment-based businesses where students are able to identify potential and types of businesses that can be developed or can be implemented based on environmental conditions 3) Teamwork in groups can foster creativity and innovation based on opportunities and risks, especially in entrepreneurship. Keywords: Eduprenenur1, Enterpreneurship2